German FDI and Integration of Production in the EU - Dietmar Keller; Rolf Jungnickel (Hamburg Institute of International Economics (HWWA), 2003)
In this paper, we investigate internationalization strategies of German manufacturing firms in the European Union. We give reasons for the hypothesis that traditional market strategies had been replaced by border-crossing production networking based on the comparative advantage of host countries and on specialisation and scale economies. Our empirical test of this hypothesis shows, on the one hand, that traditional market strategies are not outdated. On the other hand, there are clear signs of international network strategies. They form an important component in internationalization strategies of multinationals in the Internal Market. The location of foreign production of German multinationals is, among others, oriented towards the technological potential of host countries indicating the importance of asset-seeking strategies. Furthermore, the positive connection between foreign production and both exports and imports points at the significance of efficiency-oriented strategies with foreign affiliates taking over an active part and not only being recipient of components of the German parent companies. However, there is hardly evidence that significant changes towards network strategies took place between 1996 and 2000.
Keywords: F15; F21; F23; 330; Foreign Direct Investment; European Integration; Internationalization strategies; Direktinvestition; Deutsch; Multinationales Unternehmen; Wettbewerbsstrategie; Auslandsproduktion; EU-Staaten